Analysis Of Affective Commitment And Work Ethic On The Performance Of Members Of The Senyum Anak Nusantara (San) Community, Sidoarjo Chapter - Noer, Arif; Irbayuni , Sulastri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Discussions about human resources are important for the development of an organization. Low affective commitment and work ethic among the committee members of the Komunitas Senyum Anak Nusantara (SAN) Chapter Sidoarjo have led to suboptimal performance within the community. This study aims to identify and analyze the influence of affective commitment and work ethic on the performance of SAN Chapter Sidoarjo community members. This is a quantitative study with three variables: affective commitment, work ethic, and member performance, conducted on the SAN Chapter Sidoarjo community. The sampling method used non-probability sampling with a saturated sampling technique approach. Data collection was conducted through the distribution of questionnaires to all 74 members of the SAN Chapter Sidoarjo community, who served as the study population. The questionnaires were designed using a Likert scale. The data obtained were analyzed using the SEM-PLS method with the assistance of SmartPLS 4 software. The results of the study indicate that affective commitment and work ethic contribute to member performance. These findings imply the need to build and maintain members' affective commitment through personal approaches, non-material rewards, and active involvement in decision-making, as well as developing internal training programs or workshops to enhance work ethic, particularly in aspects of leadership, team collaboration, and time management.